How to understand Pakistan's hybrid regime: the importance of a multidimensional continuum. Issue 1 (2nd January 2017) - Adeney, Katharine
ABSTRACT: Pakistan has had a chequered democratic history but elections in 2013 marked a second turnover in power, and the first transition in Pakistan's history from one freely elected government to another. How do we best categorize (and therefore understand) political developments in Pakistan? Is it now safe to categorize it as an electoral democracy or is it still a hybrid case of democracy? Using the Pakistani case as an example, this article argues that hybrid regimes deserve consideration as a separate case (rather than as a diminished subtype of democracy or authoritarianism), but must be categorized along a multidimensional continuum to understand the dynamics of power within the political system.